A mesoscale study of micro-spallation of Cu through coarse-grained molecular dynamics modeling. (15th April 2022) - Chen, Pengyu; Wang, Xinxin; Wang, Pei; He, An-Min
Abstract: Micro-spallation in metals is a complex dynamic fragmentation process accompanied by shock-induced overheating and melting. However, the damage evolution involved in this process, as well as the underlying mechanism, remain poorly understood. Here, a computationally efficient coarse-grained molecular dynamics (CGMD) method is used to study the micro-spallation of Cu. We demonstrate the capability of this method to reproduce results obtained by the classical molecular dynamics (MD) method in predicting spall damage of solid Cu under shock loading. CGMD simulations, however, give a higher spall strength and a later nucleation time compared with MD simulations, owing to the higher stress required to create collective voids in the former compared with the smaller individual voids in the latter. By contrast, the calculated values (including those of the compressive pressure, strain rate, and spall strength) and the predictions of microstructural evolution during micro-spallation of Cu obtained from CGMD simulations are in good agreement with those from MD simulations. This is attributed to the temperature immediately before spallation being sufficiently high for a strong shock to exist with a dominant effect on spallation, such that the collective motion of voids in CGMD simulations has a negligible effect on spall strength. A dependence of the spall strength on the strain rate of liquid Cu is proposed. This CGMD method allows the investigation of micro-spallation of Cu at the mesoscale. Graphical abstract: Highlights: A computational efficient coarse-grained molecular dynamics (CGMD) method is used in micro-spallation. CGMD reproduces phase transformation and other fundamental features of micro-spallation. Damage evolution involved in micro-spallation is well retained by CGMD simulations. CGMD method enables us to enlarge sample length from nano-scale to hundreds of microns. Strain rate dependence of the spall strength for melted Cu is proposed.